Mechanism of Chronic Stress-Induced Glutamatergic Neuronal Damage in the Basolateral Amygdaloid Nucleus - Songjun Wang; Xia Liu; Weibo Shi; Qian Qi; Guozhong Zhang; Yingmin Li; Bin Cong; Min Zuo (Analytical Cellular Pathology)
Stress is a ubiquitous part of our life, while appropriate stress levels can help improve the body’s adaptability to the environment. However, sustained and excessive levels of stress can lead to the occurrence of multiple devastating diseases. As an emotional center, the amygdala plays a key role in the regulation of stress-induced psycho-behavioral disorders. The structural changes in the amygdala have been shown to affect its functional characteristics. The amygdala-related neurotransmitter imbalance is closely related to psychobehavioral abnormalities. However, the mechanism of structural and functional changes of glutamatergic neurons in the amygdala induced by stress has not been fully elucidated. Here, we identified that chronic stress could lead to the degeneration and death of glutamatergic neurons in the lateral amygdaloid nucleus, resulting in neuroendocrine and psychobehavioral disorders. Therefore, our studies further suggest that the Protein Kinase R-like ER Kinase (PERK) pathway may be therapeutically targeted as one of the key mechanisms of stress-induced glutamatergic neuronal degeneration and death in the amygdala.